Penerapan Metodologi Pendidikan dalam Al-Qur’an dan Hadits di Taman Pengajian Anak (TPA) Karangploso Yogyakarta - Moh irwansyaH; Wafiq Nur Ziyadatur Rohma; Karwadi Karwadi (POSTGRADUATE OF PALANGKA RAYA STATE ISLAMIC INSTITUTION, 2023)
The educational methodology in the Qur'an is part of several processes of methods taught through the Qur'an which is also one of the methods taught in the process of Islamic education. Hadith is also part of the learning method because in it there is an example, which will be a powerful method in fostering the development of students. Perfect example, is the example of the Prophet Muhammad. which can be a reference for educators as the main role model. The purpose of this study is to see how the application of the Al-Qur'an and Hadith educational methodology is in the Karangploso Children's Recitation Center, Yogyakarta. The research method used is descriptive qualitative. Data collection methods used were observation and in-depth interviews. The results of this study the researcher saw that the application of the educational methodology had run smoothly and effectively, all educational methodologies in the Qur'an and hadith were applied to the students and this had been able to shape the character of the students in accordance with the teachings contained in the Qur'an and Hadith.